Differential Ecosystem Function Stability of Ammonia-Oxidizing Archaea and Bacteria following Short-Term Environmental Perturbation - Jun Zhao (American Society for Microbiology, 2020)
ABSTRACT Rapidly expanding conversion of tropical forests to oil palm plantations in Southeast Asia leads to soil acidification following intensive nitrogen fertilization. Changes in soil pH are predicted to have an impact on archaeal ammonia-oxidizing archaea (AOA), ammonia-oxidizing bacteria (AOB), and complete (comammox) ammonia oxidizers and, consequently, on nitrification. It is therefore critical to determine whether the predicted effects of pH on ammonia oxidizers and nitrification activity apply in tropical soils subjected to various degrees of anthropogenic activity. This was investigated by experimental manipulation of pH in soil microcosms from a land-use gradient (forest, riparian, and oil palm soils). The nitrification rate was greater in forest soils with native neutral pH than in converted acidic oil palm soils. Ammonia oxidizer activity decreased following acidification of the forest soils but increased after liming of the oil palm soils, leading to a trend of a reversed net nitrification rate after pH modification. AOA and AOB nitrification activity was dependent on pH, but AOB were more sensitive to pH modification than AOA, which demonstrates a greater stability of AOA than AOB under conditions of short-term perturbation. In addition, these results predict AOB to be a good bioindicator of nitrification response following pH perturbation during land-use conversion. AOB and/or comammox species were active in all soils along the land-use gradient, even, unexpectedly, under acidic conditions, suggesting their adaptation to native acidic or acidified soils. The present study therefore provided evidence for limited stability of soil ammonia oxidizer activity following intensive anthropogenic activities, which likely aggravates the vulnerability of nitrogen cycle processes to environmental disturbance. IMPORTANCE Physiological and ecological studies have provided evidence for pH-driven niche specialization of ammonia oxidizers in terrestrial ecosystems. However, the functional stability of ammonia oxidizers following pH change has not been investigated, despite its importance in understanding the maintenance of ecosystem processes following environmental perturbation. This is particularly true after anthropogenic perturbation, such as the conversion of tropical forest to oil palm plantations. This study demonstrated a great impact of land-use conversion on nitrification, which is linked to changes in soil pH due to common agricultural practices (intensive fertilization). In addition, the different communities of ammonia oxidizers were differently affected by short-term pH perturbations, with implications for future land-use conversions but also for increased knowledge of associated global nitrous oxide emissions and current climate change concerns.